Substitusi Tepung Nangka dan Durasi Fermentasi terhadap Profil Mutu Kimia dan Sensori Roti Manis Berbasis Tepung Terigu - Irmayanti; Chairil Anwar; Irhami; Ika Rezvani Aprita (Universitas Djuanda, 2025)
Bread is one of the staple foods consumed by the Indonesian population, in addition to rice. It contains carbohydrates and serves as an important source of energy and calories. This study aimed to examine the effect of jackfruit flour substitution and fermentation duration on the chemical and sensory quality profile of wheat flour-based sweet bread. A factorial completely randomized design was used, with two factors: jackfruit flour substitution and fermentation time. The results showed that increasing the proportion of jackfruit flour led to higher ash content and improved sensory scores for color, taste, texture, and aroma, but had no significant effect on reducing moisture content. Similarly, fermentation duration increased ash content and enhanced organoleptic attributes without significantly lowering moisture. The combination of both factors improved ash content, sensory quality, and reduced moisture levels in the bread. The optimal treatment, based on panelist acceptance, was found at 15% jackfruit flour substitution and 60 minutes of fermentation, yielding the following product characteristics: moisture 19.21%, ash 1.58%, color 4.13 (like), taste 4.00 (like), aroma 4.20 (like), and texture 4.07 (like).